2018
DOI: 10.3390/genes9040214
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major Rhizobacterial Taxa Affected by a Glyphosate-Tolerant Soybean Line via Shotgun Metagenomic Approach

Abstract: The worldwide commercial cultivation of transgenic crops, including glyphosate-tolerant (GT) soybeans, has increased widely during the past 20 years. However, it is accompanied with a growing concern about potential effects of transgenic crops on the soil microbial communities, especially on rhizosphere bacterial communities. Our previous study found that the GT soybean line NZL06-698 (N698) significantly affected rhizosphere bacteria, including some unidentified taxa, through 16S rRNA gene (16S rDNA) V4 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…These methods have their base as a polymerase chain reaction (PCR), useful for amplifying a DNA region, most times through16S rRNA, subsequently followed by purification methods for analyzing endophyte communities, some of which sometimes include community fingerprinting or cloning techniques ( Gao and Tao, 2012 ). However, the biased results attributed to PCR present one of the major challenges faced in identifying these endophytes ( Lu et al, 2018 ). Currently, researchers are considering ways of combining both culture-independent and dependent approaches because each has bases inherent to it ( Reinhold-Hurek and Hurek, 2011 ).…”
Section: Challenges and Advances In Isolation And Identification Of Ementioning
confidence: 99%
“…These methods have their base as a polymerase chain reaction (PCR), useful for amplifying a DNA region, most times through16S rRNA, subsequently followed by purification methods for analyzing endophyte communities, some of which sometimes include community fingerprinting or cloning techniques ( Gao and Tao, 2012 ). However, the biased results attributed to PCR present one of the major challenges faced in identifying these endophytes ( Lu et al, 2018 ). Currently, researchers are considering ways of combining both culture-independent and dependent approaches because each has bases inherent to it ( Reinhold-Hurek and Hurek, 2011 ).…”
Section: Challenges and Advances In Isolation And Identification Of Ementioning
confidence: 99%
“…However, when GM crops grown in the field, the actual effects on the environment, such as soil, are still equivocal. Some studies reported that the cultivation of GM crops did not affect the soil microbial communities (Sohn 2016, Zhou et al 2016, Lu et al 2018a, while some studies found the difference of soil microbial communities between non-GM crops and GM crops (Lu et al 2018b, Wen et al 2019. As the soil microbial communities differed with plants, different GM crops should be analysed individually so that the effects caused by GM crops can be assessed accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Root exudation includes the secretion of enzymes, oxygen and water, ion, mucilage and diverse carbon-containing metabolites. The plant root system produces various metabolites, while the root tips secrete most of the root exudates, which are low molecular weight organic substances (such as amino acids, amides, organic acids, sugars, enzymes, phenolic acids and coumarin), high-molecular-weight compounds (such as proteins and mucilages) and other substances, including sterols that attract bacteria to the rhizosphere [26,27]. However, the components of the exudates vary in the amount released, molecular weight, and biochemical functions.…”
Section: The Rhizosphere Soil As a Treasure Trove For Bacterial Community Concentrationmentioning
confidence: 99%